An examination of major works for wind band and brass ensemble: “Legacy” by Mark Camphouse, “Concert Variations” by Claude T. Smith, and “Romance for Band” by John Zdechlik - Villareale, Rachel Margaret (Kansas State University, 2016)
The following report provides a comprehensive analysis of and teaching guide for one work for brass ensemble and two works for wind band: Legacy by Mark Camphouse, Concert Variations by Claude T. Smith, and Romance for Band by John Zdechlik. A chapter is included for each work, supplying essential information needed to properly prepare the conductor for teaching and rehearsing the work in question. Information is included regarding the composer, the composition, historical perspective, technical considerations, stylistic considerations, musical elements, form and structural analysis, listening suggestions, and a suggested seating arrangement. Outlines of rehearsal plans used by the author are included with self-evaluations of each rehearsal, in addition to a detailed score analysis grid as presented by Dr. Frank Tracz in Mark Walker's book, The Art of Interpretation of Band Music. Chapters are also devoted to the author’s philosophy of music education and philosophy of quality literature selection. All materials are included with the hope that this research can assist in preparation of these works by other conductors and ensembles, as well as to promote a more active programming of these quality, lesser-known works.
Keywords: Conducting; Analysis; Masters report; Mark Camphouse; Claude T. Smith; John Zdechlik